ANALISIS REPRESENTASI SALINGTEMAS BUKU AJAR BIOLOGI KELAS XI SMA NEGERI SEKOTA SEMARANG (FMIPA UNNES, 2012)
The purpose of this study was to identify the ‘salingtemas’ representativeness (integration of science,environment, technology and community) of biology textbooks grade XI and their compatibility with the textbook assessment instrument developed by BSNP (national board for educational standard). The study used quantitave approaches for content analysis. Sample was collected by a purposive sampling technique, obtaining two biology textbooks published by ESIS (textbook 1), and by Erlangga (textbook 2). Data were analyzed by descriptive statistic methods. The results showed that ‘salingtemas’ representativeness level of the textbook 1 and 2, of both their core and practice materials, were 48,33% and 48,135%, under middle criteria. The compatibility of their content, language, and presentation of the biology textbooks grade XI with the texbook assessment instrument from BSNP was as follows, textbook 1 was 86,21% and textbook 2 was 89,09% under highly compatible criteria. On the other hand ‘salingtemas’ representativeness of the biology textbooks was under middle criteria (quitely represented) and their compatibility with the assessment instrument of the textbook from BSNP was high (higly compatible). Penelitian ini bertujuan untuk mendeskripsikan tingkat representasi salingtemas pada buku ajar biologi kelas XI serta kesesuaian buku ajar biologi kelas XI dengan instrumen penilaian buku teks pelajaran dari BSNP. Penelitian ini menggunakan pendekatan kuantitatif dengan metode content analysis. Pengambilan sampel dilakukan dengan teknik purposive sampling, diperoleh dua buah buku ajar yaitu buku biologi terbitan ESIS (buku ajar 1), dan buku biologi terbitan Erlangga (buku ajar 2). Analisis data dilakukan dengan metode statistik deskriptif. Hasil penelitian menunjukkan tingkat representasi salingtemas dalam substansi materi dan latihan pada buku ajar 1 sebesar 48,33%; buku ajar 2 sebesar 48,135% dengan kriteria sedang. Kesesuaian isi, bahasa, penyajian dengan instrumen penilaian buku teks pelajaran dari BSNP dalam buku ajar 1 sebesar 86,21%; buku ajar 2 sebesar 89,09% dengan kriteria sangat sesuai. Kesimpulan penelitian ini menunjukan tingkat representasi salingtemas dalam substansi materi dan latihan pada buku ajar biologi kelas XI adalah sedang, dan kesesuaian isi, bahasa, penyajian buku ajar biologi kelas XI dengan instrumen penilaian buku teks pelajaran dari BSNP adalah sangat sesuai.